2022
DOI: 10.3390/medicina58111517
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival Rate of Autogenous Tooth Transplantation: Up to 162 Months

Abstract: Background and Objectives: The purpose of this study is to observe the usefulness of autogenous tooth transplantation by examining the cumulative survival rate according to the period of auto-transplanted teeth as pre-implant treatment. Materials and Methods: This study was conducted on 111 patients who visited Kyungpook National University Dental Hospital and underwent autogenous tooth transplantation between November 2008 and January 2021 (about 13 years). The cumulative survival rate of autogenous tooth tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“…4.1 CONCEITO Um transplante é definido como a transferência de um órgão ou tecido, para substituir ou compensar uma função deficiente 11 .…”
Section: Revisão De Literaturaunclassified
See 1 more Smart Citation
“…4.1 CONCEITO Um transplante é definido como a transferência de um órgão ou tecido, para substituir ou compensar uma função deficiente 11 .…”
Section: Revisão De Literaturaunclassified
“…De acordo com os estudos, as taxas de sucesso desse procedimento estão acima de 80% e os dentes submetidos a esse procedimento são capazes de exercer suas funções normais 6,10,11 .…”
Section: Introductionunclassified
“…Yanik et al found in another study that 4% of cases showed root resorption [ 5 ]. When the recipient’s immune system targets the implanted tooth’s root, root resorption takes place, which results in tooth loss [ 7 ]. The causes of failure of the autotransplant is chronic root resorption, inflammatory resorption, replacement resorption i.e., ankylosis, marginal periodontitis, apical periodontitis, caries, and trauma [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in most young patients, implant-retained restorations or fixed partial dentures are only an appropriate treatment plan in the later stages of development. For this reason, auto-transplantation can successfully replace congenitally missing teeth and teeth lost to trauma or caries in young adolescent patients [ 2 ]. Auto-transplanted teeth can also induce bone growth, which will continue as the patient matures and develops [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Auto-transplanted teeth can also induce bone growth, which will continue as the patient matures and develops [ 3 ]. When the procedure is performed correctly, success rates of revascularization are approximately 85%, and patients can expect a long-term tooth survival rate of 83–98% [ 2 , 4 , 5 ]. However, not all cases of auto-transplantation are successful.…”
Section: Introductionmentioning
confidence: 99%